Cuneiform Texts of Unpublished loans from UrIII Dynasty - Hadi Zwaid, Wafaa (Al-Adab Journal, 2019)
The research deals with a study of five cuneiform texts for unpublished loans from UrIII Dynasty (2012-2004B.C), its analysis and translation. They are from Iraq museum collection, dated back to Shusin (2037-2029B.C) and Ibisin’s (2028-2004B.C) reign, their contents are loans of barely (three texts) and silver (two texts), they are of two kinds: interest - loans (ur5 - ra) and free - interest loans (má - nu - tuk), the interest ration in loans was determined £ 33% for barely and 20% for silver.